Forgiveness and Optimism, As a Predictor of Happiness, Life Satisfaction, and Prosocial Behavior among Bank Employees - Aqsa Nadeem; Syeda Asma Gillani; Muhammad Tahzeem; Feroza Nazeer (Research Journal of Psychology, 2025)
The research study intended to investigate the notable contribution of forgiveness and optimism in happiness, life satisfaction, and prosocial behaviors of bank employees in Muzaffarabad, Azad Jammu, and Kashmir. The study incorporates a total sample size of 300 bank employees, all of whom have been consistent employees for at least six months. Demographic variables, age, gender, and education were also involved in the analysis. Data were gathered using a systematic questionnaire and evaluated using SPSS (Statistical Procedure for Social Sciences). The study explores the relationships between forgiveness, and optimism, and their impacts on life satisfaction, happiness, and prosocial behavior. The findings demonstrate significant positive associations between forgiveness and optimism with its dependent variables (life satisfaction, happiness, and prosocial behavior). Furthermore, a t-test was conducted to analyze differences in forgiveness and optimism levels between men and women and age groups. The result shows that women have a higher score on forgiveness and optimism than men and elderly adults have high levels of forgiveness and optimism. Moreover, multiple regression analysis was implemented to approach the distinct contributions of forgiveness and optimism to the prediction of life satisfaction, happiness, and prosocial behavior. The study's outcomes showed that forgiveness and optimism significantly predicted higher life satisfaction, happiness, and prosocial behavior among bank employees. These results show the necessity of encouraging forgiveness and optimism in promoting these outcomes among bank employees.